Penerapan Manajemen Mutu Terpadu Sebagai Strategi Dalam Meningkatkan Kualitas Pendidikan Di Madrasah Aliyah Nurul Barokah Cipatat - Siti Fatimah; Murdani, Denny (STIM-LPI Makassar, 2024)
Total Quality Management (TQM) is a strategic approach applied in various sectors, including education. The implementation of Total Quality Management in Madrasah Aliyah is an important issue in efforts to improve the quality of education. The purpose of this research is to analyze the implementation of Total Quality Management in improving the quality of education and how it can enhance the effectiveness and efficiency of the education process in Madrasah Aliyah Nurul Barokah Cipatat. This research uses a qualitative descriptive approach. This method is chosen because it can provide a detailed and in-depth understanding of the researched concept. In this research, data about the researched phenomenon is collected through observation, interviews, document collection, and then analyzed in-depth. The results of this research indicate that: 1) Madrasah Aliyah Nurul Barokah Cipatat has implemented a quality management system through effective leadership management. 2) The implementation of Total Quality Management to support the teaching and learning process in Madrasah Aliyah Nurul Barokah Cipatat has been successful. This quality management includes curriculum planning and outcome-oriented teaching, good education and training for educators, student-centered focus, and adequate facilities and infrastructure. 3) Madrasah Aliyah Nurul Barokah Cipatat has made significant efforts in implementing Total Quality Management to improve the quality of education. Overall, the implementation of Total Quality Management in Madrasah Aliyah Nurul Barokah Cipatat to enhance the quality of education has been successful. Although there are challenges and obstacles in its implementation, continuous evaluation and improvement efforts are being made to address these shortcomings.